The Representation of Clash of Culture in China Achebe's Things Fall Apart and NO Longer at Ease: African Literary View - Khalil, Haider Ibrahim (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2024)
The present paper traces the clash of culture and traditions in post-colonial Nigerian society in China Achebe Things Fall Apart and No longer at Ease. The paper will essentially focus on how China Achebe depicts the clash of culture that was affected by colonialism. In other words, colonialism brings new forms of cultural norms that contradict with the natives’ culture. These norms are opposed by the inherited traditions of the Nigerian society. Therefore, the paper will concentrate on the clash between the traditional cultural norms and the colonial norms that oppress the native and distort their forefathers’ identity. The paper is going to rely on Bhabha’s concept of clash of culture that involves critical arguments about the relationship between the colonized people and the colonizers. For this reason, the analysis of the cultural difference will cite some critical arguments about the clash of culture portrayed in the selected plays. The concept, accordingly, will be cited to discuss two thematic tenets in the selected plays.